Supplementation with groundnut haulms for sheep fattening in the West African Sahel - Ayantunde, Augustine A.; Delfosse, P.; Fernández Rivera, S.; Gerard, Bruno G.; Dan-Gomma, A. (Springer, 2007)
Groundnut haulms along with cowpea hay are major crop residues used for animal fattening in the West African Sahel. In traditional sheep fattening,feeds are always provided ad-hoc and in an unregulated fashion, which is rather wasteful. As a preliminary study to establish the optimal feeding levels of groundnut haulms for profitable sheep fattening, a feeding trial was conducted for 70 days with four levels of groundnut haulms (0, 150, 300 and 450 g/day) and a basal diet of bush hay. The effects of supplementation with groundnut haulms on feed intake, water consumption, live weight changes and economic return were determined. Twenty-four Peuhl Oudah rams with average initial weight of 28.6 kg (SD = 1.4) were randomly allocated to four treatments defined by the four levels of groundnut haulms in the diet. Faeces and urine were collected in weeks 5 and 9 of the trial. Digestible organic matter intake (g/(kg LW)0.75) and nitrogen intake (g/day) increased linearly with the level of groundnut haulms offered. Sheep that were fed only bush hay lost 18.4 g/day, while those that were offered 150, 300 and 450 g of groundnut haulms gained 1.4, 19.3 and 40.2 g/day, respectively. The gross return ranged from 1883 to 4946 FCFA per ram. Net benefit, after removing the feed and veterinary costs from the gross return, ranged from 368 to 1400 FCFA per ram.